Outcome of Patients Treated with Hematopoietic Stem Cell Transplantation: Results from A Single Center - Gholamreza Bahoush (Elsevier, 2021)
Objective: Hematopoietic stem cell transplantation (HSCT) is known as one of the most advanced and modern treatments in the world for various diseases which do not respond well to other therapies. Evaluating outcomes of these patients, especially in newly developed centers, can crucially help in developing and improving the quality of these centers. Methods: In a retrospective analytical cohort study, we statistically analyzed all patients treated with HSCT in the Bone Marrow Transplant Unit of the Ali-Asghar Pediatric Hospital affiliated to Iran University of Medical Sciences. The demographic information as well as all information concerning each patient's transplant process was extracted and statistically analyzed using SPSS Version 23. Results: The mean neutrophilic and platelet engraftment days were, respectively, 16 (range = 12-21) and 22 (range = 15-34) days after HSCT, while the neutrophilic engraftment occurred significantly earlier in allogeneic transplants compared to the autologous ones (P = 0.020). The total event-free survival (EFS) rate of the patients based on the median follow-up of 12 months was 11.50% ± 53.60%. Based on the total follow-up period, the estimated total EFS rate of the patients was calculated as 35.20% ± 13.50%. The estimated EFS rate was found to be better in patients who had undergone allogeneic transplantation than those who received an autologous transplant (P = 0.780). Conclusions: The HSCT results at our center are comparable to those at other centers in Iran. We argue that the facility can provide adequate therapy to patients requiring HSCT, on the proviso that some organizational limitations are addressed.